Pertanggungjawaban Tim Penjamin Mutu Dalam Penetapan Penyedia Jasa Konstruksi Pada Pengadaan Barang/Jasa Pemerintah - Wulandary, Siti Zulaika; Rembrandt, Rembrandt; Syam, Misnar (Faculty of Law, Andalas University, 2024)
This article analyses the quality assurance activity to determine the winner carried out by the Budget User. Quality assurance activity is carried out by the Quality Assurance Team, which was established by the instruction of the Minister of Public Works and Housing Number 01 of 2022. Government goods/services procurement, which is government legal action, generates state administrative decisions. This decision is often made by other parties who feel aggrieved. The existence of the Quality Assurance Team (QAT) as a government organ that participates in the process of determining the winner by Budget User is not regulated by its accountability in the process of government goods/services procurement. Therefore, the authority of QAT to determine the form of accountability is important to understand. The first result of the study is suggested that the authority of QAT in the process of government goods/services procurement in the Ministry of Public Works and Housing in the form of checking the completeness of the proposal document for determining the winner and preparing the concept of recommendation for determining winner carried out by Budget User is the authority obtained from delegation. The authority of QAT is stated as delegation because it meets the elements required to obtain delegation authority, according to experts. However, if referring to Government Administration Law, the authority given to QAT cannot be categorized as delegation because, according to Government Administration Law, delegation can only be assigned by the Government Regulation/Presidential Regulation/Regional Regulation. Second, because the authority of QAT is obtained delegatively, then QAT has legal accountability. However, the accountability of QAT is only limited to accountability for duties to the Budget User, which is in the form of internal accountability. The authority of assigning a winner, which is still carried out by the Budget User, gives the Budget User the burden of legal accountability towards the verdict issued, which is the Letter of Assigning the Winner of Provider by the Budget User.